MICRO SMALL ENTERPRISES (SMEs) DEVELOPMENT STRATEGY FOR CREATIVE INDUSTRIES IN TASIKMALAYA CITY - Rossana Tiarasari; Ma’mun Sarma; Feryanto (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Tasikmalaya City is one of the cities with a rapidly growing number of micro and small creative industry businesses in West Java Province. However, growth in micro and small industrial enterprises does not guarantee progress for the city because there are still several inhibiting factors to the progress of the sector industry, such as low-quality human and managerial resources, difficulty in accessing capital, and competition with similar businesses, which affect the competitiveness of production. The data used in this study include primary and secondary data with analysis using descriptive analysis methods, IFE, EFE, and IE matrices, SWOT analysis, and QSPM analysis. Based on the results of the IFE analysis (2.74) and EFE (2.88), the development strategy for micro and small businesses in the creative industry is in quadrant V. Namely, the strategy needed is to maintain business stability, strengthen competitiveness, and increase efficiency. The SWOT analysis produces three main strategies, namely product and market diversification, the establishment of workshops or studios that are tourist destinations, and incentive and incubation programs. The best strategy based on QSPM is product and market diversification, with the highest TAS value (6.22).